2015
DOI: 10.1039/c4sc01911c
|View full text |Cite
|
Sign up to set email alerts
|

A new pH sensitive fluorescent and white light emissive material through controlled intermolecular charge transfer

Abstract: Fabrication of a unique white light LED from a stimuli-responsive organic molecule is reported. Emission properties are dominated by the pH of the solution through intermolecular charge transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
93
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 59 publications
2
93
0
Order By: Relevance
“…Aggregation effects cause excimer emission which is strongly red or blue shifted depending on the substituent and are not captured by ESMD of single molecules [25,26]. No data exists yet exists for solvatochromic shifts in these molecules which is completely free of aggregation effects.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Aggregation effects cause excimer emission which is strongly red or blue shifted depending on the substituent and are not captured by ESMD of single molecules [25,26]. No data exists yet exists for solvatochromic shifts in these molecules which is completely free of aggregation effects.…”
Section: Resultsmentioning
confidence: 94%
“…Nonetheless, experiments from Refs. [25,26] performed with varied solvents suggest that the solvatochromic shifts without aggregation effects are larger in fluorescence than in absorption, approximately 0.2 eV and 0.05-0.1 eV, respectively. These observations are in general agreement with the simulations and the predicted shifts are of reasonable magnitude for conjugated organic molecules [1,26].…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The pK a of this OPPV has been previously estimated to be 3.3−4.0. 15 We found that, at each pH, the emission spectrum of the gel-immobilized OPPV was distinct from that of free OPPV ( Figure 5). The fluorescence spectra were collected at 4°C upon excitation at 390 nm, the wavelength where both free and gel-adsorbed OPPV displays maximum absorption across the temperatures and pHs used in this study.…”
Section: Acs Biomaterials Science and Engineeringmentioning
confidence: 93%